Біополітична реальність естетики Е. Ткачишина-Дицького - Ганошенко, Юрій Анатолійович; Ганошенко, Ю. А.; Ganoshenko, Yu. (Миколаїв: Чорном. держ. ун-т ім. Петра Могили, 2016)
Статья посвящена исследованию эстетических особенностей поэтического метатекста современного польского автора Эугениуша ТкачишинаДыцкого с позиций биополитики. В нынешней польской литературе творчество этого поэта по праву занимает свое место в каноне современного литературного процесса, однако в Украине, к сожалению, пока мало известна. Яркой особенностью творческой манеры поэта является выразительная невписанность лирического героя в систему нормативных властных схем культуры – биополитическая реальность современности не воспринимается как имманентная, а экзистенциально отрицается через образные ряды психического нездоровья, сексуальности, бездомности, межэтничности, воплощаясь в автодеструктивний форме, поскольку эстетическая реальность не позволяет преодолеть отчужденность между ведущими властными биополитических стратегиями и собственным бытием. Eugeniusz TkaczyszynDycki’s poetry is a subtle weave of different cultural codes and systems of symbolic images that makes it a kind of written existential psychoanalysis. Thus, the poetic metatext verbalizes the author’s inner experiences of abnormality, imbued with emotional shades of the protest against traditional cultural schemes of the social life, which subdues all the images and sensuality becoming the poetical dominant. Taking as the basis Michel Foucaul’st methodology together with the ideas of hermeneutics and phenomenology this article focuses on the biopolitical aspects of the semantic structure of Eugeniusz Tkaczyszyn Dycki’s metatext. Immanent inability to live according to the existing governmental strategies seems to be a specific organizational force which rationalizes (with the help of words) the personal experiences from the past: complex, unrealized and unspoken relationships with the author’s mother and his be loved ones, his inability to fit into the existing system of sociocultural gender relations as well as his unsuccessful attempts to break the vicious circle of his hopelessness existence. Such neurotic attempts to explain his own identity lead the author to perceive an increased sense of homelessness, madness and the loss of life boundaries and landmarks. Certain patterns and relationships crumble, and the new ones still cannot arise. All this makes the poet constantly express the sense of loss (realized by specific poetic techniques of constant reduplication). In a fit of creative selfdestruction, the poet increasingly exposes his «I» while sinking into internal exile. Biopolitical aesthetic brings all the dominant poetic imagery of the author, whose poems are a kind of postmodern experience, the confrontation to governmental strategies of cultural reality. Статтю присвячено розгляду естетичних особливостей поетичного метатексту сучасного польського автора Евґеніуша ТкачишинаДицького з позицій біополітики. У нинішній польській літературі творчість цього поета по праву посідає своє місце в ка ноні сучасного літературного процесу, однак в Україні, на жаль, поки що маловідома. Яскравою особливістю творчої манери поета є виразна невписаність ліричного героя в систему нормативних владних схем культури – біополітична реальність сучасності не сприймається як іманентна, а екзистенційно заперечується через образні ряди психічного нездоров’я, сексуальності, бездомності, міжетнічності, втілюючись в автодест руктивній формі, оскільки естетична реальність не дає змоги подолати відчуженість між провідними владними біополітичними стратегіями і власним буттям.
Биополитическая реальность эстетики Э. Ткачишина-Дыцкого
Biopolitical reality of E. Tkachyshyn-Dycki’s aesthetics
Keywords: біополітика; метатекст; поезія; травма; владна стратегія; культурна схема; анормативність; биополитика; метатекст; поэзия; травма; властная стратегия; культурная схема; анормативность; biopolitics; metatext; poetry; trauma; governmental strategy; cultural scheme; аnormativity